Mediating between Services and Learning Activities - the User Perspective - Falconer, Isobel; Littlejohn, Allison; Conole, Gráinne; Jeffery, Ann (Proceedings of the International Conference on Networked Learning, 2006)
We reflect upon the LADIE project’s experience of migrating a concept of user requirements from the teaching practitioner community to the technical developer community in the light of literature on ’mediating representations’ and ’mediating artefacts’. We show that the practical operation of mediating representations is far more complex than previously acknowledged. We suggest that communities need to overlap, allowing reciprocal communication, to migrate concepts via a representation. If they do not, a chain of intermediate representations and communities may be necessary. Finally, we draw a tentative distinction between mediating representations and mediating artefacts, based not in the nature of the resources, but in their mode and context of use.